Huertas familiares en el contexto de la agricultura pampeana: Caracterización de la actividad hortícola y percepción sobre los invertebrados presentes en las huertas del partido de San Antonio de Areco, Buenos Aires, Argentina = Family orchards in the context of Pampas agriculture: Characterization of horticultural activity and perception of the invertebrates present in the orchards of the district of San Antonio de Areco, Buenos Aires, Argentina - Zufiaurre, Emmanuel (2024)
In recent years, horticulture in the northern region of the Buenos Aires province, Argentina, has increased. Accurate information on this activity is a prerequisite to address potential phytosanitary problems that farmers might face. Our objectives were to characterize the orchards in the San Antonio de Areco district, located in Buenos Aires province, and to analyze the detection and perception of farmers regarding the invertebrate fauna present within them. We distributed an on-line questionnaire and received 83 responses. Based on the results obtained, we described the orchards in the study area as family/domestic, of small-scale, located in an urban/peri-urban area, directly planted as plots in the ground, operational year-round, and primarily dedicated to self-consumption. We found that recognition of biodiversity within orchards and its role in production, as well as the identification of the most harmful groups of invertebrates, vary depending on the characteristics of orchards and the individuals working to them. This information establishes a baseline upon which to make informed decisions regarding issues related to horticultural activities in the region.